Experimental assessment of heavy crude oil production using emulsion flooding - Sehlake, Portia Boitumelo (My University, 2017)
In many crude oil exploitation oil cannot be produced using its own natural drive after many years due to pressure depletion. In order to maintain the reservoir pressure and optimize the oil production, secondary oil recovery methods are usually used i.e. water injection, gas lift and reinjection of natural gas. Although, secondary oil recovery methods increase hydrocarbon production by about 35 - 45 %, they do not provide a definitive solution due to continuous pressure decrease and the excessive amount of water required. An alternative recovery technique known as tertiary recovery or enhanced oil recovery is usually used at this stage and focuses on increasing the mobility of the oil. Chemicals such as surfactants, polymers and nanoparticles are injected to improve recovery. These chemicals help improve properties of the injected fluid and its interactions with the rocks. Surfactants are well known for reducing interfacial tension formed between oil and water and polymers for improving sweep efficiency. Moreover, addition of nanoparticle is said to further reduce interfacial tension between water and oil and help reduce the capillary pressure. This study looked at emulsion stability of crude oil with cationic surfactants and non-ionic surfactants. The objective was to analyse how stable the solution with surfactants only is and also how the stability is affected by temperatures, nanoparticles and stirring mechanism. It further investigates which surfactant type is best suitable to stabilise emulsions and whether or not the combination of surfactant and nanoparticle can provide a more stable emulsion than surfactants only In the study, experiments were conducted to test emulsion stability based on temperature variation, water to oil ratios differences and droplet size formation. Cationic dodecyl trimethyl ammonium bromide (DTAB) and non-ionic Triton®X-100 surfactants were used; nanoparticle zinc oxide (ZnO) was later added into the two types of surfactants aqueous solutions and emulsion stability tests conducted. Temperature was raised from 250C to 60C to look at the effect this will have on emulsion stability. Water/ Oil ratios were analyse the effect/impact the different ratios had on emulsion stability. Droplet size distribution was analysed using a microscope to see how tight the emulsions are. The experimental results suggest that cationic DTAB is not a good candidate for emulsion stability especially at 600C. The potential application of non-ionic surfactant Triton®X-100 alone gave better stability. Addition of nanoparticle ZnO to DTAB did not help stability and when ZnO is added to non-ionic surfactant Triton®X-100 the stability was good at all temperatures but did not last for a longer periods vs having non-ionic surfactant Triton®X-100 only , suggesting that Triton®X-100 is best suitable to keep emulsions formed stable and further microscopic work supported this finding.
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Engineering (Metallurgy and Materials Engineering), October 2017
Keywords: Oil well drilling; Gasoline; Gas engineering